Evaluation of ECG random number generator for wireless body sensor networks security - Xin Chen; Yongxiang Zhang; Guanghe Zhang; Yuanting Zhang (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
In current investigations toward security, most solutions based on wireless body sensor networks (WBSNs) are relied on the application of cryptography. The generation of random numbers (RNs) and statistical test of the number's randomness are crucial part of many cryptographic systems. To guarantee the safety and reliability for WBSNs applications, it's necessary to choose an appropriate random number generator (RNG) to provide high-quality RNs. In this paper, we proposed a new RNG using the electrocardiogram (ECG) signal. We evaluated our ECG method using P-value and pass rate as the performance metrics by comparing with nine existed popular RNGs. The experimental results demonstrated that the ECG method achieved good randomness quality as some popular RNGs.